The black hunger - Pullen, Nicholas (Redhook, 2024)
"John Sackville will soon be dead. Shadows writhe in the corners of his cell as he mourns the death of his secret lover and as the gnawing hunger inside him grows impossible to ignore. He must write his last testament before it is too late. The story he tells will take us to the darkest part of the human soul. It is a tale of otherworldly creatures, ancient cults, and a terrifying journey from the stone circles of Scotland to the icy peaks of Tibet. It is a tale that will take us to the end of the world."--Page 4 of cover.